Organes de primates et frontières d’humanité. Les xénogreffes controversées du docteur Voronoff (1910 – 1930) - Catherine Rémy (Revue de Primatologie)
The French surgeon Serge Voronoff (1866-1951) made headlines in Paris during the 1920s for his attempt to transplant primate testicles in men. The surgeon was known in Great Britain too. In France, Voronoff’s experiments were generally accepted and resulted in a light-hearted celebration of the mixture of human and animal species; although accompanied by a revival of racism, which associated primates with Africans. In Great Britain, by contrast, xenotransplantations were rejected in the name of animal rights and the purity of human race.